Disease features and outcomes in United States lupus patients of hispanic origin and their mestizo counterparts in Latin America: a commentary. - Ugarte-Gil, Manuel F. (2016)
Objective. To evaluate disease features and outcomes in two populations with significant Amerindian ancestry. Methods. Hispanic patients (from Texas) from the Lupus in Minorities: Nature versus Nurture (LUMINA) cohort and Mestizo patients from the Grupo Latino Americano De Estudio del Lupus or Latin American Group for the Study of Lupus (GLADEL) cohort were included. Disease features and outcomes were evaluated at baseline and last visit. Admixture informative markers of Mestizo Genoma de Lupus Eritematoso Siste´ mico Network consortium (GENLES) patients and Hispanic LUMINA patients were compared. Univariable analyses were performed using Chi square or Student’s t test as appropriate. Multivariable analyses adjusting for possible confounders were carried out using Poisson, logistic or Cox regression models as appropriate. Results. A total of 114 LUMINA and 619 GLADEL patients were included. GLADEL patients had accrued more damage at baseline, but the opposite was the case at last visit. Being from LUMINA was a risk factor for damage accrual, even after adjusting for possible confounders [relative risk (RR) 1.33, 95% CI 1.12, 1.58]. Also, LUMINA patients have a higher risk of mortality than GLADEL patients [hazard ratio (HR) 2.37, 95% CI 1.10, 5.15], having 5-year survival of 85.6% and 94.5%, respectively. In addition, 79 LUMINA patients and 744 Mestizo GENLES patients were evaluated in order to compare genetic ancestry between the two groups; GENLES patients had a higher proportion of European ancestry (48.5% vs 43.3%, P = 0.003) and a lower proportion of Asian ancestry (3.7% vs 4.9%, P = 0.048), but the proportions of Amerindian and African ancestry were comparable in both. Conclusion. USA Hispanic patients seemed to have a poorer prognosis than their counterparts from Latin America, despite having a comparable genetic background. Socioeconomic factors may account for these observations.